Diagnostic potential of exosomal extracellular vesicles in oncology - Mickensone Andre; Allen Caobi; Jana S. Miles; Arti Vashist; Marco A. Ruiz; Andrea D. Raymond (BMC Cancer, 2024)
Abstract Liquid biopsy can detect circulating cancer cells or tumor cell-derived DNA at various stages of cancer. The fluid from these biopsies contains extracellular vesicles (EVs), such as apoptotic bodies, microvesicles, exomeres, and exosomes. Exosomes contain proteins and nucleic acids (DNA/RNA) that can modify the microenvironment and promote cancer progression, playing significant roles in cancer pathology. Clinically, the proteins and nucleic acids within the exosomes from liquid biopsies can be biomarkers for the detection and prognosis of cancer. We review EVs protein and miRNA biomarkers identified for select cancers, specifically melanoma, glioma, breast, pancreatic, hepatic, cervical, prostate colon, and some hematological malignancies. Overall, this review demonstrates that EV biomolecules have great potential to expand the diagnostic and prognostic biomarkers used in Oncology; ultimately, EVs could lead to earlier detection and novel therapeutic targets. Clinical implications EVs represent a new paradigm in cancer diagnostics and therapeutics. The potential use of exosomal contents as biomarkers for diagnostic and prognostic indicators may facilitate cancer management. Non-invasive liquid biopsy is helpful, especially when the tumor is difficult to reach, such as in pancreatic adenocarcinoma. Moreover, another advantage of using minimally invasive liquid biopsy is that monitoring becomes more manageable. Identifying tumor-derived exosomal proteins and microRNAs would allow a more personalized approach to detecting cancer and improving treatment.